Passing the ICT skills test - Ferrigan, Clive (Exeter : Learning Matters, 2011)
All trainee teachers hoping to gain Qualified Teacher Status need to pass a computerised ICT skills test. This book outlines the test requirements and explains the basic subject knowledge essential to completing the test.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Educational technology; Computer-assisted instruction; Libros electrónicos.